2010
DOI: 10.1016/j.jcf.2009.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Platelet proinflammatory activity in clinically stable patients with CF starts in early childhood

Abstract: In CF, platelet proinflammatory activity is increased at very young age already and might promote inflammation and tissue damage. On the other hand, platelets seem to downregulate the activation of their most important integrin (alpha(IIb)beta(3)) for clot formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…Sturm et al found a higher sP-selectin concentration in 54 CF patients—including children—compared with 55 age- and sex-matched healthy subjects [21]. In the subgroup of subjects aged 15–41 years the values compared as follows ( n CF  = 28; n HS  = 29): 41 ng/mL [2556] versus 29 ng/mL [1760].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sturm et al found a higher sP-selectin concentration in 54 CF patients—including children—compared with 55 age- and sex-matched healthy subjects [21]. In the subgroup of subjects aged 15–41 years the values compared as follows ( n CF  = 28; n HS  = 29): 41 ng/mL [2556] versus 29 ng/mL [1760].…”
Section: Discussionmentioning
confidence: 99%
“…However, in the same subjects, they found normal levels of sVCAM-1. An inverse correlation between forced expiratory volume in 1 s (FEV1) and sP-selectin was also described [20] as well as higher sP-selectin levels in CF compared with healthy controls [21]. The above findings come from few studies with moderate sample sizes.…”
Section: Introductionmentioning
confidence: 99%
“…The early onset of chronic inflammation in the CF patients is mainly mediated by neutrophils and even platelets have been suggested [42]. Proinflammatory molecules of the innate immune system such as IL-1, IL-6 and IL-8 are elevated in CF, all of which could be regulated by serine peptidases.…”
Section: Discussionmentioning
confidence: 99%
“…These data provide further evidence for platelet defects in CF which to date CF have included increased aggregability, alterations in cell lipids, decreased exocytosis, and decreased integrin binding. [4, 5] Our techniques appear sound as blood cytokine levels, VEGF and TGF-β 1 release measured during platelet aggregation, and correlation coefficients of serum VEGF and TGF-β 1 with platelet number in healthy controls are typical of those reported in other investigations. [22, 24, 32–35]…”
Section: Discussionmentioning
confidence: 60%
“…As others have reported, we found platelet counts, maximal platelet aggregation, plasma TGF-β 1 and VEGF, and unadjusted serum levels of TGF-β 1 and VEGF to be higher in CF patients. [5, 24] However, when we adjusted serum levels for platelet counts we found no differences between CF and healthy subjects. [21] This differs from the situation seen in cancer patients, where the platelet content of VEGF has also been shown to be increased in subjects with high serum VEGF levels even after adjustment for platelet counts.…”
Section: Discussionmentioning
confidence: 92%